Ferrous iron‐ and ammonium‐rich diffuse vents support habitat‐specific communities in a shallow hydrothermal field off the Basiluzzo Islet (Aeolian Volcanic Archipelago). Issue 5 (6th April 2017) - Bortoluzzi, G.; Romeo, T.; La Cono, V.; La Spada, G.; Smedile, F.; Esposito, V.; Sabatino, G.; Di Bella, M.; Canese, S.; Scotti, G.; Bo, M.; Giuliano, L.; et al.
Abstract: Ammonium‐ and Fe(II)‐rich fluid flows, known from deep‐sea hydrothermal systems, have been extensively studied in the last decades and are considered as sites with high microbial diversity and activity. Their shallow‐submarine counterparts, despite their easier accessibility, have so far been under‐investigated, and as a consequence, much less is known about microbial communities inhabiting these ecosystems. A field of shallow expulsion of hydrothermal fluids has been discovered at depths of 170–400 meters off the base of the Basiluzzo Islet (Aeolian Volcanic Archipelago, Southern Tyrrhenian Sea). This area consists predominantly of both actively diffusing and inactive 1–3 meters‐high structures in the form of vertical pinnacles, steeples and mounds covered by a thick orange to brown crust deposits hosting rich benthic fauna. Integrated morphological, mineralogical, and geochemical analyses revealed that, above all, these crusts are formed by ferrihydrite‐type Fe 3+ oxyhydroxides. Two cruises in 2013 allowed us to monitor and sampled this novel ecosystem, certainly interesting in terms of shallow‐water iron‐rich site. The main objective of this work was to characterize the composition of extant communities of iron microbial mats in relation to the environmental setting and the observed patterns of macrofaunal colonization. We demonstrated that iron‐rich deposits contain complex and stratified microbial communities with a high proportion of prokaryotes akin to ammonium‐ and iron‐oxidizing chemoautotrophs, belonging to Thaumarchaeota, Nitrospira, and Zetaproteobacteria . Colonizers of iron‐rich mounds, while composed of the common macrobenthic grazers, predators, filter‐feeders, and tube‐dwellers with no representatives of vent endemic fauna, differed from the surrounding populations. Thus, it is very likely that reduced electron donors (Fe 2+ and NH4 + ) are important energy sources in supporting primary production in microbial mats, which form a habitat‐specific trophic base of the whole Basiluzzo hydrothermal ecosystem, including macrobenthic fauna.